Risiko Kredit sebagai Pemoderasi Pengaruh Kecukupan Modal pada Profitabilitas dalam Masa Pandemi Covid-19 - Budiadnyani, Ni Putu; Arlita, I G A Desy (E-Jurnal Akuntansi; Vol 33 No 3 (2023)DO - 10.24843/EJA.2023.v33.i03.p11, 2023)
The challenge faced by banks as financial institutions is the financial performance report in which the public will choose a bank with better financial performance because the risks faced will be smaller. This study aims to examine the effect of capital adequacy on profitability and to test the ability of credit risk as a moderating variable. The number of samples analyzed was 376 samples in the form of quarterly financial reports from Rural Banks (BPR) in Badung Regency, Bali Province. The sampling technique in this study is the nonprobability sampling method with a purposive sampling technique with the criteria of a credit bank that has published quarterly published financial reports periodically for the 2020-2021 period. The analysis technique used is simple linear regression and Moderated Regression Analysis (MRA). The results showed that capital adequacy has a positive effect on profitability. However, credit risk is unable to moderate the effect of capital adequacy on profitability. Keywords: Capital Adequacy; Credit Risk; Profitability